Prevalence and Factors Associated With Fatigue in Patients With Inflammatory Bowel Disease: A Multicentre Study. (5th February 2019) - Chavarría, C; Casanova, M J; Chaparro, M; Barreiro-de Acosta, M; Ezquiaga, E; Bujanda, L; Rivero, M; Argüelles-Arias, F; Martín-Arranz, M D; Martínez-Montiel, M P; Valls, M; Ferreiro-Iglesias, R; et al.
Abstract: Background and Aims: The aims of this study were to determine the prevalence of fatigue in patients with inflammatory bowel disease [IBD], to identify the factors associated with fatigue and its severity, to assess the impact of fatigue on quality of life [QoL], and to evaluate the relationship between fatigue and sleep disorders. Methods: This was a prospective multicentre study conducted at 22 Spanish centres. Consecutive patients followed at IBD Units were included. Fatigue was evaluated with the Fatigue Severity Scale [FSS] and the Fatigue Impact Scale [FIS]. Quality of life and sleep quality were assessed using the IBD Questionnaire-Short Form [IBDQ-9] and the Pittsburgh Sleep Quality Index [PSQI], respectively. Results: A total of 544 consecutive adult IBD patients were included [50% women, mean age 44 years, 61% Crohn's disease]. The prevalence of fatigue was 41% (95% confidence interval [CI] = 37–45%). The variables associated with an increased risk of fatigue were: anxiety [OR = 2.5, 95% CI = 1.6–3.7], depression [OR = 2.4, 95% CI = 1.4–3.8], presence of extraintestinal manifestations [EIMs] [OR = 1.7, 95% CI = 1.1–2.6], and treatment with systemic steroids [OR = 2.8, 95% CI = 1.4–5.7]. The presence of EIMs [regression coefficient, RC = 8.2, 95% CI = 2.3–14.2], anxiety [RC = 25.8, 95% CI = 20.0–31.5], depression [RC = 30.6, 95% CI = 24.3–37.0], and sleep disturbances [RC = 15.0, 95% CI = 9.3–20.8] were associated with severity of fatigue. Patients with fatigue had a significantly decreased IBDQ-9 score [ p < 0.001]. Conclusions: The prevalence of fatigue in IBD patients is remarkably high and has a negative impact on QoL. Therapy with systemic steroids is associated with an increased risk of fatigue. The severity of fatigue is associated with anxiety, depression, sleep disorders, and the presence of EIMs. Fatigue was not associated with anaemia, disease activity or anti-TNF therapy.